A rare case of yellow nail syndrome in the emergency room setting: A case report - Jordan S. Elmowitz; Michael E. Nelson (JEM Reports)
Background: Yellow nail syndrome (YNS) is a rare condition that consists of the following triad: yellowing of the nails, lymphedema, and pulmonary disease. The disease may be difficult to diagnose as all three components of the triad may not be present simultaneously, and on initial evaluation, it can mimic common conditions such as onychomycosis, psoriasis, and lichen planus. This is a case of yellow nail syndrome in the emergency department. Case report: This is a case of a 31-year-old male who presented to the emergency room with a chief complaint of bilateral lower extremity swelling, yellow discoloration of his fingernails, and productive cough. Why should an emergency physician be aware of this?: Recognition of the constellation of findings can avoid unnecessary testing, exposure to potentially harmful inappropriate medications, and provide psychologic relief to the patient. Subsequently, this may reduce patient cost, avoid unnecessary side effects, and lead to appropriate disease management.